Influences of visual non-verbal information on feeling and degree of transmission in presentations. (2018) - Seki, Kazuyuki; Okubo, Masashi
It is well known that non-verbal information is important for smoothing communication. On the other hand, it is also suggested that limiting transmitted non-verbal information leads to accurate comprehension. In this research, in order to investigate the influence of visual non-verbal information in presentations on audiences' comprehension, we prepared the four videos in which the presenter was represented differently: normal, shadow, stick figure, and voice-only. Experimental participants answered questionnaires and comprehension tests after watching each presentation video. Then we verified answers from two points of view: feeling of transmission and degree of transmission. The results showed that the normal video was more highly evaluated than the other three types of videos in terms of feeling of transmission. However, the shadow video resulted in a higher degree of transmission than the other three types of videos. Furthermore, we also performed post-experiment-questionnaires and tests one week later and verified the effects of visible non-verbal information on memorability and memory retention.